«Mi potrete dire se i colori sono compartiti sul gusto francese […] avendone voi veduti di fatti». Filippo Juvarra’s projects for the Mansi Patronage in Lucca - Alessandra Del Nista (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2015)
Juvarra visited Lucca for the first time in 1706, when Coriolano Orsucci introduced him into society, and he returned there in 1714, 1724 and 1728.